Main Criteria for The Professional Orientation of Students in Teaching Natural Sciences - Karimova N.A; Xolboyeva V.Sh (Next Scientists International Journal EIJP, 2026)
This article analyzes the main criteria for the professional orientation of students in the process of teaching natural sciences. In particular, issues of identifying students' interests and abilities, involving them in practical activities, ensuring interdisciplinary integration, and forming professional competencies based on modern pedagogical technologies are highlighted. It also demonstrates effective methods for developing students' independent thinking, problem-solving, and a conscious approach to career choice. The results of the study serve to improve vocational guidance in the teaching of natural sciences.